THE ROLE OF GAME-BASED TECHNOLOGIES IN DEVELOPING BASIC ENGLISH LANGUAGE COMPETENCIES - Shamsuddinova Diyoraxon Yorqinbek qizi; Sayfulloyeva Nilufar Zexniddin qizi (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Game-based technologies have emerged as transformative tools in the domain of language education, particularly in enhancing basic English language competencies. This article explores the significance of incorporating game-based learning approaches into English language teaching, emphasizing their impact on motivation, engagement, and skill acquisition. By leveraging interactive and immersive environments, educators can create dynamic learning experiences that cater to diverse learning styles and linguistic backgrounds. The findings underscore the necessity of integrating these technologies into curricula to foster language proficiency and critical thinking among learners.